Where are you from?: locating the young adult self within and beyond the text. Issue 3 (3rd May 2016) - Spring, Erin
Abstract : This article explores the interconnections between young adult (YA) fiction and three YA readers' constructions of place within and beyond the text. It employs a qualitative, multiple case study design, and utilizes discussion groups, semi-structured interviews, and the creation of place-journals to interpret some of the ways in which three YA readers, from two contrasting Canadian communities, respond to how place and place-identity are construed within their own lives, and within two YA fiction texts. Drawing on geography theory and reader-response criticism, it offers a critical description of the moment in time when these texts, these readers, and the researcher met as part of a reading transaction, within a particular time and space. I argue that these YA readers are aware of the role of place within their own lives, and that they use these individualized constructions to shape their encounters with these texts.